(untitled) (Journal of Plant Disease Sciences, 2023)
Safflower is a major oil seed crop grown mostly on residual soil moisturein Maharashtra,Karnataka, Andhra Pradesh and Telangana in India. Diseases affecting the crop include fungal, bacterial, viral, and nematode. The main biotic challenges limiting its production are leafspot infections caused by Chowdhury, which result in significant loss of seed quality and quantity. Todifferentiate saffloweradvanced breeding lines against a field experiment was conducted at All India Coordinated Research Project on Safflower, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani with 26 advanced breeding lines and four checks Manjira (Susceptible check), SSF-658, A-1, and PBNS-12. The entries were sowed in the last week of August with spacing 30 x 15 cm, and a conducive condition was maintained for disease development. The safflower entries exhibited varying reactions against Out of 26 entries, 7entries PBNS- 148, SAF-P-1805, SAF-P-1907, SAF-19-13, PBNS-182, SAF-P-1802, SAF-P-1803 exhibited tolerant reactions, 02 entries SAF-P-1804, TSF-89 showed susceptible reaction and 17 entries showed highly susceptible reactions.None of the safflower entries was found to be immune orresistant or moderately resistant to the disease.